2007
DOI: 10.1074/jbc.m610225200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cδ Is Required for Survival of Cells Expressing Activated p21

Abstract: Inhibition of protein kinase C (PKC) activity in transformed cells and tumor cells containing activated p21RAS results in apoptosis. To investigate the pro-apoptotic pathway induced by the p21 RAS oncoprotein, we first identified the specific PKC isozyme necessary to prevent apoptosis in the presence of activated p21RAS . Dominant-negative mutants of PKC, short interfering RNA vectors, and PKC isozyme-specific chemical inhibitors directed against the PKC␦ isozyme demonstrated that PKC␦ plays a critical role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 54 publications
4
103
1
Order By: Relevance
“…Our results strongly suggest that phosphorylation of K-RasG12V is important to stimulate transformation, mobility, apoptosis resistance upon adriamycin treatment and to favor proliferation and survival at low growth factor concen- Calmodulin inhibits K-Ras phosphorylation B Alvarez-Moya et al tration. Our data agree with the fact that in some tumor cell lines, such as MIA-PaCa2 or HCT116, PKC activity stimulates cell survival and proliferation provided that K-RaG12V is expressed (Liou et al, 2004) or with some other reports in which it was demonstrated that PKC functions as a critical anti-apoptotic signal transducer in cells containing activated K-Ras, promoting cell survival through PI3K/PDK1/AKT pathway (Xia et al, 2007(Xia et al, , 2009. In contrast to previously published data (Bivona et al, 2006), phospho-mimetic K-Ras expression did not induce apoptosis in our cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…Our results strongly suggest that phosphorylation of K-RasG12V is important to stimulate transformation, mobility, apoptosis resistance upon adriamycin treatment and to favor proliferation and survival at low growth factor concen- Calmodulin inhibits K-Ras phosphorylation B Alvarez-Moya et al tration. Our data agree with the fact that in some tumor cell lines, such as MIA-PaCa2 or HCT116, PKC activity stimulates cell survival and proliferation provided that K-RaG12V is expressed (Liou et al, 2004) or with some other reports in which it was demonstrated that PKC functions as a critical anti-apoptotic signal transducer in cells containing activated K-Ras, promoting cell survival through PI3K/PDK1/AKT pathway (Xia et al, 2007(Xia et al, , 2009. In contrast to previously published data (Bivona et al, 2006), phospho-mimetic K-Ras expression did not induce apoptosis in our cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, PKC␦ has been shown to support survival by inducing activation of Akt in cells with a constitutively activated Ras pathway (29). These data together indicate that Akt may be a mediator of the PKC␦ effects.…”
Section: Pkc␦ and Pkc⑀ Support Survival Of Mda-mb-231 Cells-mentioning
confidence: 87%
“…It has been reported that PKC␦ is required for survival of mouse fibroblasts with mutated constitutively activated Ras by mediating Akt activation (29). Furthermore, ERK1/2 has been shown to suppress Akt phosphorylation in many breast cancer cell lines (28).…”
Section: Discussionmentioning
confidence: 99%
“…PI 3-kinase-dependent activation of Akt is mediated by PKC-␦, which is required for cell survival in various cancer and immune cells (1,2,28). However, Zhong et al suggested that PKC-␦ downregulation suppresses apoptotic signals through a novel PI 3-kinase-independent survival pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…rotein kinase C (PKC)-␦, a ubiquitously expressed isoform of the novel PKC subfamily, mediates an anti-apoptotic signaling cascade through the phosphatidylinositol 3-kinase (PI 3-kinase)-mediated survival pathway (1,2) and also promotes apoptosis by interfering with Akt signaling (3)(4)(5).…”
mentioning
confidence: 99%